Effects of Musculoskeletal Disorders, Workload, and Work Fatigue on Radiographer’s Performance in Kediri:A Cross-Sectional Study - Anggi Tiur; Sholicudin; Indasah; Agustin Widyowati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2026)
In Indonesia, there are still radiographers whose performance is not good and has not met the targets set by the hospital. The poor performance of radiographers is partly caused by various complaints of Musculoskeletal Disorders (MSDs), workload, and work fatigue, which affect the health and performance of radiographers. This can certainly cause dissatisfaction with the services provided and can reduce the trust of patients and their families. The purpose of this study was to determine the effect of complaints of Musculoskeletal Disorders (MSDs), workload, and work fatigue on the performance of radiographers in Kediri. The type of research used was quantitative observational analytical research. The research design used was a cross-sectional study. The population in this study were all radiographers who were members of PARI in Kediri, totaling 150 people. The sample size in this study was 108 radiographers who were members of PARI Kediri using the simple random sampling technique based on the Krejcie & Morgan table. The dependent variable in this study was performance, while the independent variables were complaints of Musculoskeletal Disorders (MSDs), workload, and work fatigue. The instrument in this study used a questionnaire sheet. Data analysis used multiple linear regression analysis. From the results of the study that have been explained above, it can be stated that the variables of Musculoskeletal Disorders (MSDs), workload, and work fatigue together have a significant effect on performance with a sig. p value > 0.05. It is hoped that hospital management can continue to improve the performance of radiographers in the radiology installation. Radiographers must always pay attention to their health and maintain a healthy lifestyle to avoid work fatigue and varioushealth problems such as Musculoskeletal Disorders (MSDs). Keywords : Musculoskeletal Disorders (MSDs), workload, work fatigue, performance